2011
DOI: 10.1080/15599612.2011.604114
|View full text |Cite
|
Sign up to set email alerts
|

An Automatic Inspection Method for the Fracture Conditions of Anisotropic Conductive Film in the TFT-LCD Assembly Process

Abstract: In this study an automatic optical inspection system is presented to evaluate the fracture and deformation status of conducting particles of anisotropic conductive film in the TFT-LCD assembly process. The amount of deformation and quantity of conducting particles in the test pattern can be automatically evaluated by image analysis. A specific operation is carried out in the image processing method, and the calculation of the image gradient operator is used to produce a preferable contrast between the processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 16 publications
(14 reference statements)
0
10
0
Order By: Relevance
“…The overall optical field combination should be very similar to the sunset spectrum. The rays through the diffuser become soft and uniform [16].…”
Section: Resultsmentioning
confidence: 99%
“…The overall optical field combination should be very similar to the sunset spectrum. The rays through the diffuser become soft and uniform [16].…”
Section: Resultsmentioning
confidence: 99%
“…Particle inspection aims to estimate the distribution and quantity of validly deformed particles and then to determine whether a good conductive circuit is formed between IC and glass substrate [7], [9]. Many works have devoted to the research of automatic particle detection [7], [9]- [11]. These works are reviewed briefly as follows.…”
Section: Related Workmentioning
confidence: 99%
“…For instance, a standard template of the validly deformed particle is constructed and template matching [7] is applied to detect the presence of the particles. In the work of Lin et al [9], the particle features are extracted with the Prewitt operators. Then Otsu algorithm [12] is used to obtain the binarized image.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In the LCD polarizer plate attaching process, the prevalent problem of bubbles between the glass substrate and the polarizer plate, due to uneven attachment, often causes quality deviations in the LCD of color image light leakage. Lin et al proposed a method to evaluate the fracture and deformation status of conducting particles of anisotropic conductive lm in the TFT-LCD assembly process [3]. Takatsuji and Arai found that holes in Al thin lms will a ect the TFT characteristics [4].…”
Section: Introductionmentioning
confidence: 99%